Field efficacy of a new deltamethrin long lasting insecticidal net (LifeNet©) against wild pyrethroid-resistant Anopheles gambiae in Benin - DJENONTIN, TOGNIHOU ARMEL; Moiroux, Moiroux; BOURAÏMA, Aziz; Zogo, Barnabas; Sidick, Ibrahim; Corbel, Vincent; Pennetier, Cédric (My University, 2018)
Background: Malaria vector control is mostly based on Long-Lasting Insecticidal Nets (LLIN). To date, all LLINs fully recommended by the World Health Organization Pesticide Scheme (WHOPES) are made of polyester or polyethylene. In this context, a new LLIN named LifeNet©, made of polypropylene fiber is developed. According to the manufacturer, LifeNet©is made of soft filament, has a greater mechanical strength, a superior insecticide wash resistance with a short insecticide regeneration time, a better flammability profile and a better environmental profile compared to polyester or polyethylene nets. Methods: Through a WHOPES supervised trial, the efficacy of LifeNet© was evaluated in Benin in experimental huts against free-flying wild mosquitoes. Results: LifeNet© has equal or better performances in terms of wash resistance, exophily, blood feeding inhibition and mortality compared to conventionally treated nets (CTN) treated with deltamethrin at 25 mg/m2 and washed to just before exhaustion. Conclusions: The efficacy of LifeNet© observed in this trial indicates that this net fulfill World Health Organization Pesticide Scheme (WHOPES) requirement for Long Lasting technology in Phase II. Throughout a Phase III trial currently ongoing in Southern Benin, the durability and the acceptability of this long-lasting insecticidal mosquito nets will be assessed under community conditions.
Keywords: Deltamethrin; Long lasting insecticidal net; LifeNet©; Pyrethroid-resistant; Anopheles gambiae; Benin